2020
DOI: 10.28991/hij-2020-01-03-01
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Blade Trailing Edge Flap Design Concept using Flexible Torsion Bar and Worm Drive

Abstract: In this paper, a simple but effective trailing edge flap system was proposed. This preliminary concept uses a more practical and stable actuation system which consists of a motor-driven worm gear drive and flexible torsion bar. The flexible torsion bar is designed to be easily twisted while keeping bending rigidity as a sup-port and the worm gear drive not only provides a high torque to overcome aero-dynamic forces on the flap area and the torsional rigidity of the support bar, but also acts as a brake to avoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 8 publications
(9 reference statements)
0
14
0
Order By: Relevance
“…The experimental research constitutes an important source of information about the performance of the test subject under various working conditions. The theoretical analysis of the issue allows defining the number of knowledge gaps in the existing research methods and indicating new areas to be examined [30,31]. It is important to properly plan the research and its implementation according to a specific pattern [32].…”
Section: Experimental Researchmentioning
confidence: 99%
“…The experimental research constitutes an important source of information about the performance of the test subject under various working conditions. The theoretical analysis of the issue allows defining the number of knowledge gaps in the existing research methods and indicating new areas to be examined [30,31]. It is important to properly plan the research and its implementation according to a specific pattern [32].…”
Section: Experimental Researchmentioning
confidence: 99%
“…Further studies on the shockwaves flow in an aeration chute spillway have shown that the deployment of the aeration intensifies the shockwaves. e waves become larger with the increase of the Froude number [27,28]. Wu et al [29] conducted experiments to study shockwaves characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…They observe significant improvement in resistive capacity and ductility for non reinforce beams over reinforced beams. Also, the change in design like blade edge and adding edged on the torsional bar helps improve mechanical properties of components used in various engineering applications [20].…”
Section: Introductionmentioning
confidence: 99%